Synergetic effect of Li doping and Ag deposition for enhanced visible light photocatalytic performance of g-C3N4. (February 2017) - Ma, Wenzhe; Wang, Xiuying; Zhang, Feng; Fei, Xu; Zhang, Xiufang; Ma, Hongchao; Dong, Xiaoli
Graphical abstract: Highlights: g-C3 N4 was modified via combining Li doping and Ag deposition. The effect of doping Li in g-C3 N4 on the structure and optical property was studied. The composite exhibited superior visible light photocatalytic activity. The synergistic effects of Li doping and Ag deposition were discussed. Abstract: g-C3 N4 modified with Li doping and Ag deposition has been successfully prepared via a facile and cost-effective method. The composite presents the excellent photocatalytic performance for the degradation of Rhodamine B. The introduction of Li and Ag could effectively increase the absorbance in the visible light region, inhibit the recombination of photogenerated electron–hole pairs and improve the generation of reactive oxidation species. The synergetic effect between the Li doping and Ag deposition gives birth to the enhancement of photocatalytic activity of g-C3 N4 .